Tanggap Pertumbuhan Bibit Kopi Robusta (Coffea Robusta L.) Terhadap Berbagai Media Tanam Dan Frekuensi Penyiraman - Lia Karlina Br Sembiring; Rosita Sipayung; Irsal (Jurnal Pertanian Tropik, 2018)
Massive breeding is often the case with the availability of the amount of water that can be stored on the media. The aim of this research is to know the influence of media and the frequency of watering on the growth of robusta coffee seedlings and to find the best media and optimum watering frequency. This experiment was conducted at the Faculty of Agriculture, University of Sumatera Utara, Medan from June to September 2017. The experimental method used was Factorial Randomized Block Design with 2 treatment factors, ie 1: planting medium ie, topsoil ; topsoil: sand (2: 1); topsoil: rice husk (2: 1), topsoil: charcoal husk (2: 1) and factor 2: watering frequency ie, watered once a day; watered every 4 days; watered 7 days and watered once every 10 days. The variable was plant height, stem diameter, total leaf number, total leaf area, fresh crown weight, canopy dry weight, fresh root weight, root dry weight, longest root, and canopy and root ratio. The results showed that planting media treatment had a significant effect on plant height variables, stem diameter increase, leaf number, total leaf area, fresh crown weight, canopy dry weight, fresh root weight, root dry weight, and root canopy ratio. The best treatment of planting medium was found in topsoil treatment: rice husk (2: 1). The treatment of watering frequency had a significant effect on the stem diameter 2 - 12 of the week after planting move observation variable, total leaf area, fresh crown weight, dry crown weight, fresh root weight, and dry weight of roots. The best treatment frequency of watering hose is watering every 4 days. The interaction between the two treatments had a significant effect on the diameter of the stem diameter variable, the total leaf area and the fresh weight of the canopy.